Effectiveness of QR Code-Based Prisoner Data Management System: Implementation of Community Service at Class IIB Pangkalan Brandan Prison, Indonesia - M. Alfarozy Syahputra; Tengku Adlin Ahmad Albab (Yayasan Bayt Shufiya Nusantara, 2025)
Manual inmate record-keeping systems frequently generate errors, delays, and low data accuracy, despite the fact that correctional security requires information that is fast, precise, and easily verifiable. Digitalization through QR Code technology offers a practical solution to these inefficiencies. This study aims to evaluate the effectiveness of QR Code implementation in supporting inmate identification and strengthening the security system at Class IIB Pangkalan Brandan Detention Center. The method employed is based on Community Service activities, consisting of system planning, the creation of room-based QR Codes, officer training, field implementation, and technical–operational evaluation. The findings indicate that QR Codes enhance identification accuracy by eliminating input errors, accelerate data verification from several minutes to mere seconds, and enable real-time monitoring of inmate presence, thereby strengthening early detection of disciplinary violations. In addition, the system improves officers’ digital literacy, resulting in a workflow that is more transparent, accountable, and secure. These achievements confirm that QR Code technology is a viable innovation for replication in other correctional facilities with appropriate adjustments.